Thematic cartography and geovisualization - Slocum, Terry A.; McMaster, Robert Brainerd 1956-; Kessler, Fritz, C.; Howard, Hugh H. (CRC Press, Taylor & Francis Group, 2023)
Given the extensive developments that have taken place in cartography and GIS in the last decade, the fourth edition of a well-established book in cartography explores the continued evolution of the Internet and Web 2.0. A new chapter on Geovisual Analytics captures the analysis and visualization of Big Data, while a new chapter on Cartography, Technology, and Society reviews the critical and ethical issues involved with collecting, using, and storing digital data; the importance of participatory cartography; and web-based geospatial data sources. Thoroughly revised, this book equips educators and benefit students with the most valuable up-to-date learning resource available in the cartographic field. Short Blurb The fourth edition of a well-established book in cartography explores the continued evolution of the Internet and Web 2.0 and captures the analysis and visualization of Big Data. Thoroughly revised, this textbook equips educators and benefit students with the most valuable up-to-date learning resource available in the cartographic field.